PSYCHOLOGY OF MUSLIM INVESTORS IN STOCK INVESTMENT DURING COVID-19 PANDEMIC - Purnama Ramadani Silalahi; Muhammad Hafizh; Salman Nasution; Sugianto Sugianto (Institute for Research and Community Empowerment (LPPM TAZKIA), 2020)
The main purpose of this study is to analyze and evaluate the psychology of Muslim investors in stock investments during COVID-19 pandemic. This research uses data collected through online questionnaires conducted in May 2020, and employ Path Analysis to make sense of the data. This study finds that the psychology of Muslim investors investing in stock markets during the COVID-19 pandemic is irrational and intuitive. Muslim investors react quickly without resorting to any fundamental/technical analysis. Muslim investors are willing to take risks and cut losses in this situation. In addition, the psychology of Muslim investors with respect to religiosity is at the second level of Homo Islamicus' self-interest, namely Al-Nafs Al-Lawamah.